Maxillofacial Surgery - Assael, Leon (IntechOpen, 2012)
Oral and maxillofacial surgery is a specialty rooted in dentistry and forged in academic medical centers in departments of surgery, as the surgical specialty well equipped to care for conditions of the mouth, jaws, head and neck. Today oral and maxillofacial surgeons are advancing cancer care, neurosciences, understanding the pathology of the region, managing congenital and acquired deformities among others. In the process this specialty is improving the lives of our patients with better function, appearance, self esteem and longevity.